Description of Parenting Patterns on Stunting and Normal Children in the Specific Area Stunting of Pasaman and West Pasaman District, West Sumatra - Masrul Masrul (Universitas Andalas, 2018)
Stunting is the effect of a systemic condition of chronic malnutrition which affects about a quarter of children under five years of age worldwide. There are 7.6 million (37%) Indonesian children suffering from stunting and the rate of stunting in West Sumatra is above the national figure of 46.1%. That number shows that many children need more attention, because they don't grow well. The nutrition intervention program that has been running so far has not been able to optimally improve the condition of stunting children. The purpose of this study was to determine the profile of parenting stunting and the difference with normal children in the specific area of stunting Pasaman and Pasaman Barat District. This study was conducted through several stages, which is data collection using a questionnaire. From this study shown that breastfeeding and complementary feeding are almost no different from groups stunting with normal children; good parenting, health and psychosocial stimulation are still lacking; the socioeconomic level of stunting children is lower than normal children. It is hoped that in the future prevention of intrautrin can be carried out by maintaining quality intake and health status; keep the intake in a balanced nutritional status, especially aspects of animal protein; and maintaining environmental sanitation and optimal parenting from the family.